Real-life experience with ixekizumab in plaque psoriasis: a multi-center, retrospective, 3-year study. (3rd April 2023) - Caldarola, Giacomo; Chiricozzi, A; Megna, M; Dapavo, P; Giunta, A; Burlando, M; Malagoli, P; Dini, V; Mariani, M; Fabbrocini, G; Quaglino, P; Bianchi, L; et al.
ABSTRACT: Background: Confirmatory data on the long-term effectiveness and safety of ixekizumab in psoriatic patients from real-world studies are needed. Objectives: The primary aim was to evaluate the 3-year drug survival of ixekizumab in the treatment of patients with moderate-to-severe plaque psoriasis, in a multicenter real‐world setting. The secondary aim was to assess the influence of predictive factors on the drug survival of ixekizumab. Methods: A retrospective analysis was performed on a cohort of patients with chronic plaque psoriasis, who received at least one dose of ixekizumab before December 2018. The drug survival analysis was performed and descriptively analyzed using Kaplan–Meier survival curves. Multivariable Cox regression analyses were carried out including variables considered to be of clinical importance. Results: A total of 306 patients were enrolled. The overall drug survival at 12, 24, and 36 months of treatment with ixekizumab was 92.11%, 83.85%, and 80.19%, respectively. A higher probability (HR 2.34) of drug withdrawal was found among patients who had already received an anti-IL-17 agent compared with bio-naive patients (p 0.017). Conclusions: We found that ixekizumab is a biological agent characterized by long-term effectiveness, not influenced by several clinical factors and associated with a good safety profile.